Cytogenetics abnormalities in a referred population for chromosomal analysis and the role of fluorescence in-situ hybridization in refining the diagnosis. Issue 1 (January 2017) - Mohamed, Amal M.; Kamel, Alaa K.; Helmy, Nivine A.; Hammad, Saida; Kayed, Hesham F.; Shihab, Marwa; El-Gerzawy, Assad; Eid, Maha M.; Eid, Ola M.; Mekkawy, Mona K.; Mahmoud, Wael; Mazen, Inas; et al.
Abstract : Introduction: This study presents the frequency of chromosomal abnormalities in 12 884 patients referred to Genetics Clinics at National Research Centre over 10 years. This study aimed to assess the frequency and types of chromosomal abnormalities in referred cases, determine whether fluorescence in-situ hybridization (FISH) refined the clinical diagnoses, and compare our findings with those of similar studies. Patients and methods: On the basis of the reason for referral, patients were classified into one of the following six groups: intellectual disability/multiple congenital abnormalities (31.4%), disorders of sex development (24%), genetic counseling because of a previously affected child (10%), repeated abortions (10%), premarital counseling (9.2%), and a miscellaneous group (15.4%). Results: The total proportion of chromosomal abnormalities was 19.3% and included autosomal anomalies (78.5%), numerical anomalies (50.5%), and structural anomalies (28%). Sex chromosome anomalies accounted for 21.5%, numerical anomalies for 15.7%, and structural anomalies for 5.8%. FISH increased the detection of chromosomal abnormalities by 0.4%, confirmed cytogenetics abnormalities, and identified sex chromosome abnormalities in disorders of sex development, the origin of the marker chromosome, and the near break points in translocations. Conclusion: Conventional cytogenetics and FISH could diagnose ∼20% of our referred population; still, most of these patients need further genetic diagnoses. The application of multiplex ligation-dependent probe amplification, array comparative genomic hybridization, and next-generation sequencing will allow for more accurate genetic testing.